PROFESSIONAL ACTIVITIES OF A MATHEMATICS TEACHER - Ergashev, A. A.; Poʻlatova Zarifaxon Xayotxon qizi (Researchparks Publishing, 2023)
Methodical training of mathematics teacher in pedagogical university is a part of his/her professional preparation for future professional activity. Therefore, this article consistently analyzes such concepts as